Improved Teacher Scientific Publication Competency Based On Sustainable Professional Development at Tanbisaw - Riry Sriningsih (Fakultas MIPA Universitas Negeri Padang, 2018)
Based on observations, the results of questionnaires and discussions with elementary school teachers in Tanbisaw, Kubung Subdistrict, Solok Regency, found two main factors causing the majority of teachers to be heavy and difficult to publish their writings, namely: 1) Motivation and 2) Substance. Most teachers state that procedures for making scientific works and publications have criteria that are too difficult to fulfill or follow. The teacher has not found any material that is worth writing. The teacher stated that they did not have the time to do research and look for reading sources to write. The purpose of this activity is to motivate and improve the competence of teachers in producing scientific publications in carrying out their duties through Sustainable Professional Development. Specifically, the aim is to: 1) direct teachers to produce research ideas, 2) guide teachers in compiling scientific publications, and 3) inform and direct teachers to publish works at national seminars and scientific journals. The activity was held at SDN 02 Tanjung Bingkung, with participants being elementary school teachers consisting of 8 elementary schools, the methods used were: lecture methods, guided training, discussion and direct practice in writing and making scientific papers to be published.